PANDANGAN ADONIS TERHADAP PUISI DAN MODERNITAS - Moh. Kanif Anwari (Adabiyyāt: Jurnal Bahasa dan Sastra, 2012)
Poetry is a mirror of a society. It contains the poets’ emotions, thought, and impression poured through the medium of language. This paper describes the thought of Ali Ahmad Said, who is better known as Adonis, on Arabic poetry from the perspectives of literature, linguistics, culture, and philosophy. The study begins by describing Adonis’ biography, followed by a description and analysis of Arabic poetry, its forms and relation to religion and modernity. The formulated problems concerns who Adonis is, how the position of Arabic poetry in relation with culture (religion) is, and how the modernity of Arabic poetry is. Using descriptive analytical method and making al-Shi’riyya al-‘Arabiyya the main reference, the paper comes to a conclusion that Adonis is a person who tends to reject the establishment in many facets of the Arabs’ life and further encourage them to accept changes. Arabic poetry serves as a more effective medium for the authority to establish the public religiosity. With all its traditionalism, Arabic poetry turns out to show its modernity because it maintains a high plurality and never ending creativity.